Associations between supportive and undermining coparenting and controlling feeding practices. (1st October 2021) - Tan, Cin Cin; Herzog, Noelle K.; Mhanna, Asmaa
Abstract: Parents play an important role in shaping child eating and weight outcomes through feeding practices. Controlling feeding practices are positively related to child obesogenic eating and obesity risk. Although many parents' characteristics have been examined in relation to controlling feeding practices, less is known about the role of coparenting. The current study seeks to examine whether coparenting (supportive versus undermining) predict controlling feeding practices (use of food for emotion regulation, food as a reward, pressure to eat, restriction for health, restriction for weight). A total of 160 parents (56% females) of preschool-aged children between 3- and 5-years old completed an online survey. After accounting for parent characteristics (i.e., sex, BMI, age), regression analyses showed that supportive coparenting was not predictive of controlling feeding practices. However, regression analyses showed that undermining coparenting predicted greater use of food for emotion regulation, food as a reward, and restriction for weight, but was not predictive of pressure to eat and restriction for health. Implications associated with these findings are discussed.